High resolution mapping and identification of candidate genes for the BaMMV/BaYMV-resistance gene rym13 and Ryd3 involved in BYDV-tolerance of barley - Färber, Sandra; Justus Liebig University Giessen (My University, 2019)
Barley yellow mosaic disease, caused by Barley mild mosaic virus (BaMMV} and Barley yellow mosaic virus (BaYMV}, and barley yellow dwarf, caused by Barley yellow dwarf virus (BYDV}, are important diseases of barley causing high yield losses. As BaMMV and BaYMV are transmitted by the soil-borne plasmodiophorid Polymyxa graminis and BYDV by aphids, the only environmently sound way to prevent these yield losses is breeding for resistant/tolerant cultivars.In this thesis, high resolution mapping and candidate gene analysis for the BaMMV/BaYMV resistance gene rym13 and the BYDV tolerance conferring gene Ryd3 was conducted. For rym13, a high resolution mapping population based on 5,191 F plants was established and marker saturation was conducted by mapping the flanking markers to published genomic resources of barley. Using these genomic resources in combination with next-generation- sequencing-techniques led to a fast saturation of the resistance harbouring interval and identification of candidate genes. Analysing phenotypic and genotypic data revealed an independent inheritance of the BaMMV and BaYMV resistance in the cultivar ´Taihoku A´. Two candidate genes for rym13, co-segregating with BaMMV resistance in an independent population, were identified.Regarding Ryd3, the former mapping population established by Lüpken et al. (2014) was extended to 7,427 F plants. After mapping the co-segregating markers to the published reference genome of barley, the interval related to tolerance was shortened to 104.14 mio bp. This interval harbours a number of candidate genes. For further investigations to unravel the mechanism of tolerance, a TILLING population was established in the course of this thesis.This study lays the foundation for subsequent isolation and validation of rym13 and Ryd3.

Die Gelbmosaikvirose der Gerste, verursacht durch Barley yellow mosaic virus (BaYMV) und Barley mild mosaic virus (BaMMV) und die Gelbverzwergung der Gerste, verursacht durch Barley yellow dwarf virus (BYDV) führen zu erheblichen Ertragsverlusten. Aufgrund der Übertragung durch den bodenbürdigen Plasmodiophorid Polymyxa graminis im Falle der Gelbmosaikvirose bzw. durch Blattläuse (Gelbverzwergung) ist die Züchtung resistenter bzw. toleranter Sorten die einzige ökologisch und ökonomisch sinnvolle Möglichkeit hohe Ernteverluste zu verhindern.Im Rahmen dieser Arbeit wurde die hochauflösende Kartierung und die Identifikation von Kandidatengenen für das BaMMV Resistenzgen rym13 sowie das BYDV Toleranzgen Ryd3 durchgeführt.Für die Kartierung von rym13 wurde eine hochauflösende Kartierungspopulation, bestehend aus 5.191 F Pflanzen, erstellt. Durch Verankerung der flankierenden Marker in bereits veröffentlichten genomischen Ressourcen für Gerste in Kombination mit der Verwendung von next-generation-sequencing Techniken (GBS, WGS) konnte das resistenzgentragende Intervall verkürzt und co-segregierende Kandidatengene identifiziert werden. Die Analyse der phänotypischen und genotypischen Daten ergab außerdem eine unabhängige Vererbung der BaMMV und BaYMV- Resistenz in der widerstandsfähigen Elternlinie ´Taihoku A´. Nach Kartierung in einer unabhängigen Validierungspopulation stellten sich zwei Gene als vielversprechende Kandidaten für rym13 heraus.Zur Feinkartierung von Ryd3 wurde die Anzahl der F Pflanzen der Kartierungspopulation von Lüpken et al. (2014) auf 7.427 Pflanzen erhöht. Nach Verankerung der Marker in der Referenzsequenz der Gerste (Mascher et al. 2017) konnte das toleranzgentragende Intervall auf 104,14 mio bp eingeschränkt werden. Auf Grund der großen Anzahl an Genen in diesem Intervall sind hier weiterführende Analysen notwendig, um Ryd3 zu isolieren. Zu diesem Zweck wurde im Rahmen der Arbeit eine TILLING-Population erstellt und steht nun für weitere Experimente zur Verfügung.Zusammenfassend stellt diese Arbeit eine essenzielle Grundlage für die Isolation von rym13 und Ryd3 dar.
Keywords: ddc:630